73.2k views
5 votes
Six years after a tree was planted, its height was 7 feet. Nine years after it was planted, its height was 16 feet. Which of the following equations gives the height y, in feet, of the tree after x years if the tree grows at a constant rate? Check all of the boxes that apply.

y – 6 = 3(x – 10)

y – 16 = 3(x – 9)

y = 3x – 11

y = –3x – 23

2 Answers

6 votes

Answer:

b c

Explanation:

User SAPLogix
by
6.1k points
0 votes

Answer:

it is

y-16=3(x-9)

y=3x-11

b & c

User Guillem Xercavins
by
5.8k points